Gastropods from the solimÕes formation (Upper miocene), acre basin, Brazil - Sousa, Felipe Nascimento [UNESP]; Marques, Rodrigo Cesar; Ribeiro, Victor Rodrigues [UNESP]; Gaia, Geovane Augusto [UNESP]; Guilherme, Edson; Maciente, Andréa; DE SOUZA-FILHO, Jonas Pereira; Hsiou, Annie Schmaltz; Ghilardi, Renato Pirani [UNESP] (Sociedade Brasileira de Paleontologia, 2021)
A taxonomic review of Miocene gastropods from the Solimões Formation, Acre Basin, Brazil, from specimens collected at Cachoeira do Bandeira, Oriente, and an outcrop named Spot 04, is here presented. Three ampullariid species (Pomacea maculata, P. planorbula, Pomacea sp.), one thiarid species (Aylacostoma sp.), and one cochliopid species (Sioliella sp.) are identified for these deposits. These gastropod are known to occur in freshwaters environments, thus consolidating the hypothesis of a non-influence of brackish water on the upper Miocene deposits of the Acre Basin. The previous identification of P. maculata and Aylacostoma sp. is changed here considering biometrical analyses and shell morphological descriptions. The first report of Sioliella in this basin increases the gastropod fauna known for these strata and expands the range of this genus.
Keywords: Ampullariidae; Aylacostoma; Cochliopidae; Pomacea; Sioliella; Thiaridae